Intertextuality, authenticity and Gonzo Selves in Anya Ulinich's Lena Finkle's Magic Barrel. Issue 2 (1st December 2015) - Brauner, David
This article traces the intertextual relationships between Anya Ulinich's graphic novel Lena Finkle's Magic Barrel, Bernard Malamud's short story 'The Magic Barrel' and a number of works by Philip Roth. Through these relationships and her construction of a number of variations on what Miriam Libicki has called a 'gonzo self' Ulinich explores the tensions between life and art, fact and fiction, and autobiography and the novel, mediating the aesthetic imperatives of what Roth has called the 'written world' and the ethical obligations of the 'unwritten world' in order to arrive at an authentic sense of herself as an artist and writer.